Development of a Stable Respiratory Syncytial Virus Pre-Fusion Protein Powder Suitable for a Core-Shell Implant with a Delayed Release in Mice: A Proof of Concept Study - Max Beugeling; Katie Amssoms; Freek Cox; Ben De Clerck; Ellen Van Gulck; Jeroen A. Verwoerd; Guenter Kraus; Dirk Roymans; Lieven Baert; Henderik W. Frijlink; Wouter L. J. Hinrichs (MDPI AG, 2019)
Currently, there is an increasing interest to apply pre-fusion (pre-F) protein of respiratory syncytial virus (RSV) as antigen for the development of a subunit vaccine. A pre-F-containing powder would increase the flexibility regarding the route of administration. For instance, a pre-F-containing powder could be incorporated into a single-injection system releasing a primer, and after a lag time, a booster. The most challenging aspect, obtaining the booster after a lag time, may be achieved by incorporating the powder into a core encapsulated by a nonporous poly(dl-lactic-co-glycolic acid) (PLGA) shell. We intended to develop a stable freeze-dried pre-F-containing powder. Furthermore, we investigated whether incorporation of this powder into the core-shell implant was feasible and whether this system would induce a delayed RSV virus-neutralizing antibody (VNA) response in mice. The developed pre-F-containing powder, consisting of pre-F in a matrix of inulin, HEPES, sodium chloride, and Tween 80, was stable during freeze-drying and storage for at least 28 days at 60 °C. Incorporation of this powder into the core-shell implant was feasible and the core-shell production process did not affect the stability of pre-F. An in vitro release study showed that pre-F was incompletely released from the core-shell implant after a lag time of 4 weeks. The incomplete release may be the result of pre-F instability within the core-shell implant during the lag time and requires further research. Mice subcutaneously immunized with a pre-F-containing core-shell implant showed a delayed RSV VNA response that corresponded with pre-F release from the core-shell implant after a lag time of approximately 4 weeks. Moreover, pre-F-containing core-shell implants were able to boost RSV VNA titers of primed mice after a lag time of 4 weeks. These findings could contribute to the development of a single-injection pre-F-based vaccine containing a primer and a booster.